2018
DOI: 10.1136/heartjnl-2018-313189
|View full text |Cite
|
Sign up to set email alerts
|

Effects and costs of real-time cardiac telerehabilitation: randomised controlled non-inferiority trial

Abstract: REMOTE-CR is an effective, cost-efficient alternative delivery model that could-as a complement to existing services-improve overall utilisation rates by increasing reach and satisfying unique participant preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
521
3
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(635 citation statements)
references
References 25 publications
8
521
3
10
Order By: Relevance
“…In a randomised study of standard CR versus remotely-monitored CR, the telemedicine approach was non-inferior to the standard CR approach as assessed by exercise status, maximum oxygen consumption, and waist and hip circumference at completion of the programme (figure 4). 6 Programme and medication costs were lower for the telemedicine CR with no difference in hospitalisation costs. Lavie, Kachur and Milani7 congratulate the authors on this study and comment that “Certainly, more comprehensive Remote-CR models, including home, internet and community-based programmes, are needed to provide alternatives to conventional, medically supervised, facility-based Standard-CR.…”
mentioning
confidence: 84%
“…In a randomised study of standard CR versus remotely-monitored CR, the telemedicine approach was non-inferior to the standard CR approach as assessed by exercise status, maximum oxygen consumption, and waist and hip circumference at completion of the programme (figure 4). 6 Programme and medication costs were lower for the telemedicine CR with no difference in hospitalisation costs. Lavie, Kachur and Milani7 congratulate the authors on this study and comment that “Certainly, more comprehensive Remote-CR models, including home, internet and community-based programmes, are needed to provide alternatives to conventional, medically supervised, facility-based Standard-CR.…”
mentioning
confidence: 84%
“…However, it must be mentioned that there is much more to learn about what makes mHealth applications appealing and how these interventions can be used for long-term cardiovascular disease management. 3 Videoconferencing offers the additional advantage of enabling providers to see and hear their patients (and vice versa); it can enable you to develop a therapeutic rapport, get a sense of a patient's health and well-being, supervise exercise remotely (either through videoconferencing software demonstrated by Hwang et al 4 or via a bespoke telerehabilitation platform and remote monitoring devices demonstrated by Maddison et al 5 ) and provide feedback and support, as well as share screens and files for educational and counselling purposes and to illustrate required actions. Videoconferencing also allows for groups, 3 therefore enhancing efficiency and providing the opportunity for participants to share experiences.…”
Section: Future-proofing Cardiac Rehabilitation: Transitioning Servicmentioning
confidence: 99%
“…Therefore, although the improvements in psychological risk factors were correlated with improvements in exercise capacity, nevertheless, all patients also received the other non-exercise aspects of Standard-CR. Whether all of the benefits would be similar to Remote-CR was not assessed in the Maddison et al ’s5 study, but at least we know HRQoL did at least improve similarly to that with Standard-CR.…”
mentioning
confidence: 95%
“…In their Heart paper, Maddison and colleagues5 from Australia and New Zealand report on a randomised controlled trial of CRET, with telerehabilitation (Remote-CR) and centre-based CRET (Standard-CR) in 162 participants, where exercise capacity or peak oxygen consumption (peak VO 2 ), CHD risk factors, exercise adherence, motivation, HRQoL, and interventions, hospital utilisations and medication costs were all assessed and compared in both groups. After completion of both programmes, most parameters, importantly peak VO 2 , were similar in both groups, whereas waist and hip circumference was lower in Standard-CR, and Remote-CR patients were less sedentary at 24 weeks.…”
mentioning
confidence: 99%
See 1 more Smart Citation